Comparing the application of mNGS after combined pneumonia in hematologic patients receiving hematopoietic stem cell transplantation and chemotherapy: A retrospective analysis - Zhang, Binglei; Gui, Ruirui; Wang, Qian; Jiao, Xueli; Li, Zhen; Wang, Juan; Han, Lu; Zhou, Ling; Wang, Huili; Wang, Xianjing; Fan, Xinxin; Lyu, Xiaodong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Rapid and accurate pathogen identification is essential for timely and effective treatment of pneumonia. Here, we describe the use of metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage (BALF) fluid to identify pathogens in patients with hematologic comorbid respiratory symptoms in a retrospective study with 84 patients. In the transplantation group, 8 cases (19.5%) and 47 cases (97.9%) were positive for BALF by conventional method detection and mNGS detection, respectively, and 6 cases (14.0%) and 41 cases (91.1%) in chemotherapy group, respectively. The detection rate of mNGS in both groups was significantly higher than that of conventional detection methods (all P＜0.05). Pseudomonas aeruginosa and Streptococcus pneumoniae were the most common bacterial infections in the transplantation and chemotherapy groups, respectively. Aspergillus was the most common fungal infection in both groups. Human betaherpesvirus 5 (HHV-5), torque teno virus and human betaherpesvirus 7 (HHV-7) were the most common pathogen species in both groups. The most common type of infection in patients in the transplantation and chemotherapy groups was the mixed infection of bacteria-virus. Most patients in the transplantation group had mixed infections based on multiple viruses, with 42 cases of viral infections in the transplantation group and 30 cases of viral infections in the chemotherapy group, which were significantly higher in the transplantation group than in the chemotherapy group (χ2=5.766, P=0.016). and the mixed infection of virus-virus in the transplantation group was significantly higher than that in the chemotherapy group (27.1% VS 4.4%, P=0.003). The proportion of death due to pulmonary infection was significantly higher in the transplantation group than in the chemotherapy group (76.9% vs 16.7%, χ2=9.077, P=0.003). This study demonstrated the value of mNGS of BALF in improving the diagnosis and prognosis of hematologic comorbid pneumonia, helping patients to obtain timely and effective treatment, and giving guidance on the overall treatment plan for patients, with particular benefit for patients with hematologic chemotherapy comorbid pneumonia.